Parents in adult psychiatric care and their children: a call for more interagency collaboration with social services and child and adolescent psychiatry. (2nd January 2018) - Afzelius, Maria; Östman, Margareta; Råstam, Maria; Priebe, Gisela
Abstract: Background: A parental mental illness affects all family members and should warrant a need for support. Aim: To investigate the extent to which psychiatric patients with underage children are the recipients of child-focused interventions and involved in interagency collaboration. Methods: Data were retrieved from a psychiatric services medical record database consisting of data regarding 29, 972 individuals in southern Sweden and indicating the patients' main diagnoses, comorbidity, children below the age of 18, and child-focused interventions. Results: Among the patients surveyed, 12.9% had registered underage children. One-fourth of the patients received child-focused interventions from adult psychiatry, and out of these 30.7% were involved in interagency collaboration as compared to 7.7% without child-focused interventions. Overall, collaboration with child and adolescent psychiatric services was low for all main diagnoses. If a patient received child-focused interventions from psychiatric services, the likelihood of being involved in interagency collaboration was five times greater as compared to patients receiving no child-focused intervention when controlled for gender, main diagnosis, and inpatient care. Conclusions: Psychiatric services play a significant role in identifying the need for and initiating child-focused interventions in families with a parental mental illness, and need to develop and support strategies to enhance interagency collaboration with other welfare services.